Measurement of Capillary Wetting Rate in Fibrous Assemblies - TAGAWA, Mieko; GOTOH, Keiko (Journal of Home Economics of Japan, 2001)
The capillary wetting rates of water/ethanol mixtures into fibrous assemblies were determined from the changes in weight due to wetting. Silica filters untreated and silanized with three silane coupling agents, γ-aminopropyltriethoxysilane (APTES), methyltriethoxysilane (MTES) and perfluoroethyltri-methoxysilane (FETMS), were used as fibrous assemblies. The advancing contact angles on a silica single fiber and the surface free energies for water/ethanol mixtures were measured by the Wilhelmy and the pendant drop techniques, respectively. A strip of the silica filter was suspended from the arm of the electrobalance and the weight was automatically recorded during the contact of the lower edge of the strip with water/ethanol mixtures. The weight of water/ethanol mixtures penetrated into the silica filter increased with time and showed saturation. The weight was converted into volume using the density of water/ethanol mixtures, and was used as a measure of the capillary wetting rate. The rates were found to depend on the contact angle, the surface free energy and the viscosity of water/ethanol mixtures. By comparing the results of the untreated filter with those of the silanized filters, it was shown that the viscosity of water/ethanol mixtures in the vicinity of the fiber surface was associated with the capillary wetting rate.